2011
DOI: 10.1039/c0cp01720e
|View full text |Cite
|
Sign up to set email alerts
|

Structures and reaction mechanisms of glycerol dehydration over H-ZSM-5 zeolite: a density functional theory study

Abstract: The initial stage of glycerol conversion over H-ZSM-5 zeolite has been investigated using density functional theory (DFT) calculations on an embedded cluster model consisting of 128 tetrahedrally coordinated atoms. It is found that glycerol dehydration to acrolein and acetol proceeds favourably via a stepwise mechanism. The formation of an alkoxide species upon the first dehydration requires the highest activation energy (42.5 kcal mol(-1)) and can be considered as the rate determining step of the reaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 42 publications
(50 reference statements)
0
59
2
Order By: Relevance
“…In the case of acrolein, even though recently values have been reported for ΔH°f by means of computational chemistry methods by Vasiliu et al [73], and later by Lewars and Liebman [84], the subsequent calculations in this work were carried out with data obtained with the Joback method due to its result (ΔH°f = −65.4 kJ·mol −1 ) which is in very good agreement with the value reported by Lewars and Liebman [84] (ΔH°f = −65 kJ·mol −1 ). Although 1,3-DHP, 2,3-DHP, vinyl alcohol, and 3-HP are not final reaction products in glycerol dehydration, they have been proposed as intermediate compounds by other authors [25][26][27]53] but there is a lack of their thermodynamic properties in the literature. From the equations of the Joback method in Table A1 and the values of Table A3, the values for ΔH°f, ΔG°f, and Cp were calculated for each species involved in the reactive system and presented in Table A5.…”
Section: Appendix a Estimation Of Thermodynamic Properties Of Pure Omentioning
confidence: 97%
See 3 more Smart Citations
“…In the case of acrolein, even though recently values have been reported for ΔH°f by means of computational chemistry methods by Vasiliu et al [73], and later by Lewars and Liebman [84], the subsequent calculations in this work were carried out with data obtained with the Joback method due to its result (ΔH°f = −65.4 kJ·mol −1 ) which is in very good agreement with the value reported by Lewars and Liebman [84] (ΔH°f = −65 kJ·mol −1 ). Although 1,3-DHP, 2,3-DHP, vinyl alcohol, and 3-HP are not final reaction products in glycerol dehydration, they have been proposed as intermediate compounds by other authors [25][26][27]53] but there is a lack of their thermodynamic properties in the literature. From the equations of the Joback method in Table A1 and the values of Table A3, the values for ΔH°f, ΔG°f, and Cp were calculated for each species involved in the reactive system and presented in Table A5.…”
Section: Appendix a Estimation Of Thermodynamic Properties Of Pure Omentioning
confidence: 97%
“…The thermodynamic data for water, methanal, and ethanal were obtained from the literature [75]. In the case of acrolein, even though recently values have been reported for ∆H • f by means of computational chemistry methods by Vasiliu et al [73], and later by Lewars and Liebman [84], the subsequent calculations in this work were carried out with data obtained with the Joback method due to its result (∆H [25][26][27]53] but there is a lack of their thermodynamic properties in the literature. From the equations of the Joback method in Table A1 and the values of Table A3, the values for ∆H • f , ∆G • f , and C p were calculated for each species involved in the reactive system and presented in Table A5.…”
Section: Appendix a Estimation Of Thermodynamic Properties Of Pure Omentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Several studies have been reported in recent years on solid-acid catalysts such as metal phosphates, 4-7 metal sulfates, 4,8 metal oxides, 4,[9][10][11] supported heteropolyacids (HPAs), 4,[12][13][14][15][16][17][18][19] and zeolites 4,[20][21][22][23] for the dehydration of glycerol to acrolein in the gas phase. Most of these catalysts exhibit superior dehydration activities with higher water/glycerol ratios in the feed at moderate temperatures.…”
Section: Introductionmentioning
confidence: 99%